The Relationship between Sleep and Cognitive Performance in Autism Spectrum Disorder (ASD): A Pilot Study - Nouf Backer Al Backer; Malak Alzawad; Hafiz Habibullah; Shahid Bashir (MDPI AG, 2018)
Background: Sleep concerns are common in children with autism spectrum disorders (ASD). The impact of poor sleep on cognitive performance in ASD children is not well-established. We investigated the possible correlation between sleep quality in ASD children and cognitive performance. The Cambridge Neuropsychological Test Automated Battery (CANTAB) was administered to examine specific components of non-verbal cognition. Methods: The Children's Sleep Habits Questionnaire (CSHQ) and actigraphy-measured data from 18 children with diagnosis of ASD were evaluated. Motor planning task (MOT), simple reaction time task (SRT) and the intradimensional/extradimensional shift (IED) of CANTAB were administered. Results: ASD good sleeper (ASD-GS) showed significant better response time for SRT task as compared to ASD poor sleeper (ASD-PS) based on CSHQ score. Parameters of bedtime resistance (r = 0.531, p = 0.023), sleep anxiety (r = 0.474, p = 0.047) from CSHQ and actigrapgy dependent (wake after sleep onset (WASO) (r = 0.430, p = 0.024) were significantly correlate with response time of SRT task. Conclusion: We conclude that some signs reflecting the presence of poor sleep in ASD correlate with various aspects of motor output on non-verbal performance tasks. The question is raised whether poor sleep in non-complaining persons with autism should be treated.